Future challenges of road transport - Kung, Christine Sui Mei; Melan, Mustakim (2012)
The dependency of human towards road transportation is rising in their daily life. Road is currently mode of transportation that is as flexible and functional in the transportation systems.As the scarcity of the land through the increasing for urbanization, at the same time, road transportation faces challenges with the increasing of fuel prices, safety of vehicles, road capacity and the environment issues (Emission).The purpose of this study is to analyze the challenges of the future road transportation through reviewing on the case studies, books, information for website and consultation from expert.